Pengaruh Penerimaan Dana Ziswaf, NPF Nett, dan Pendapatan Musyarakah Terhadap NPF Gross dengan Firm Size Sebagai Variabel Moderasi Periode Tahun 2018.Q1 – Tahun 2023.Q3 - Sella Haniifatul Ariiqoh; Eka Wahyu Hestya Budianto (Institut Agama Islam Negeri Ponorogo, 2025)
Introduction: This study aims to determine the effect of ZISWAF Fund Revenue, NPF Nett, and Musyarakah Income on NPF Gross with Firm Size as a Moderating Variable. Research Methods: The sample used in this study is a company in the financial sector registered with the Financial Services Authority (OJK) in 2015.Q1 to 2023.Q3. The data analysis technique used is Panel Data Regression Analysis and Moderated Regression Analysis (MRA) with the Eviews 12 application. Results: The results showed that ZISWAF Fund Revenue and NPF Nett had a positive effect on NPF Gross for the period 2018.Q1-2023.Q3. Musyarakah financing and firm size has a negative effect on NPF Gross for the period 2018.Q1-2023.Q3. Firm Size is able to moderate ZISWAF Fund Revenue and Musyarakah Income on NPF Gross for the period 2018.Q1-2023.Q3. Conclusion: Firm Size is able to moderate ZISWAF Fund Revenue and Musyarakah Income. Future research is expected to use other variables as moderating variables, such as dividend policy and use company samples from other sectors.